Post-Amarna Period Statues of Amun and His Consorts Mut and Amunet - Eaton-Krauss, Marianne, (Harvard Egyptological Studies ;, 2020)
The reign of the "heretic pharaoh" Akhenaten-the so-called Amarna Period-witnessed an unprecedented attack on the cult of Amun, King of the Gods, with his cult center at ancient Thebes (modern Luxor). A program to reinstate Amun to pre-eminence in the traditional pantheon was instituted by Akhenaten's successors Tutankhamun, Ay, and Horemhab. Damaged reliefs and inscriptions were restored and new statues of Amun and his consorts Mut and Amunet commissioned to replace those destroyed under Akhenaten. In this study, over 60 statues and fragments of statues attributable to the post-Amarna Period on the basis of an inscription, physiognomy, and/or stylistic analysis are discussed, as well as others that have been incorrectly assigned to the era.